The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2011
DOI: 10.1002/stem.587
|View full text |Cite
|
Sign up to set email alerts
|

A Targeted NKX2.1 Human Embryonic Stem Cell Reporter Line Enables Identification of Human Basal Forebrain Derivatives

Abstract: We have used homologous recombination in human embryonic stem cells (hESCs) to insert sequences encoding green fluorescent protein (GFP) into the NKX2

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
101
0

Year Published

2011
2011
2017
2017

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 97 publications
(103 citation statements)
references
References 58 publications
(93 reference statements)
2
101
0
Order By: Relevance
“…In order to generate a tool for the identification and purification of candidate human lung progenitors, we used gene editing technologies to target an enhanced green fluorescence reporter (GFP) gene to the endogenous human NKX2-1 locus in multiple human PSC lines. Prior reports of targeting GFP to the NKX2-1 locus in human PSCs for the derivation of forebrain lineages resulted in NKX2-1 haploinsufficiency (17). Hence, pursuing a strategy designed to retain intact expression of targeted loci without haploinsufficiency ( Figure 1A and Supplemental Figure 1A; supplemental material available online with this article; https:// doi.org/10.1172/JCI89950DS1), we targeted an exon3-2A-GFP cassette to the second intron of NKX2-1 using either transcription activator-like effector nucleases (TALENs) or CRISPR-Cas9 tools deployed in ESCs (H9) or in our previously published iPSC lines: cystic fibrosis patient-specific C17 iPSCs (18) and normal BU3 iPSCs ( Figure 1 and Supplemental Figure 1) (19).…”
Section: Resultsmentioning
confidence: 99%
“…In order to generate a tool for the identification and purification of candidate human lung progenitors, we used gene editing technologies to target an enhanced green fluorescence reporter (GFP) gene to the endogenous human NKX2-1 locus in multiple human PSC lines. Prior reports of targeting GFP to the NKX2-1 locus in human PSCs for the derivation of forebrain lineages resulted in NKX2-1 haploinsufficiency (17). Hence, pursuing a strategy designed to retain intact expression of targeted loci without haploinsufficiency ( Figure 1A and Supplemental Figure 1A; supplemental material available online with this article; https:// doi.org/10.1172/JCI89950DS1), we targeted an exon3-2A-GFP cassette to the second intron of NKX2-1 using either transcription activator-like effector nucleases (TALENs) or CRISPR-Cas9 tools deployed in ESCs (H9) or in our previously published iPSC lines: cystic fibrosis patient-specific C17 iPSCs (18) and normal BU3 iPSCs ( Figure 1 and Supplemental Figure 1) (19).…”
Section: Resultsmentioning
confidence: 99%
“…To gain further insight into the nature of hypothalamic patterning, we differentiated an NKX2-1:: GFP reporter cell line (Goulburn et al, 2011) to hypothalamic progenitors and immunostained for GFP and hypothalamic transcription factors. This analysis revealed that 68±5% of RAX-immunopositive cells, 15±7% of OTP-immunopositive cells and 51±16% of SIM1-immunopositive cells expressed GFP (supplementary material Fig.…”
Section: Directed Differentiation Of Hpscs Into Hypothalamic Progenitorsmentioning
confidence: 99%
“…Using differentiation protocols modeled after mouse studies, several laboratories have also attempted to produce MGE-like interneurons from human ESCs (Goulburn et al 2011;Germain et al 2013;Liu et al 2013a;Maroof et al 2013;Nicholas et al 2013;Kim et al 2014) and human-induced pluripotent stem cells (iPSCs) (Fig. 3) (Liu et al 2013b).…”
Section: In Vitro Sources Of Inhibitory Cortical Interneuronsmentioning
confidence: 99%
“…Three other studies have taken advantage of an hESC line, in which GFP was inserted into the Nkx2-1 locus to facilitate identification of ventral forebrain progenitors (Goulburn et al 2011;Maroof et al 2013;Nicholas et al 2013). Nkx2-1 is a homeodomain transcription factor enriched in embryonic MGE of mouse and human, as well as in thyroid, lung, and diencephalon.…”
Section: In Vitro Sources Of Inhibitory Cortical Interneuronsmentioning
confidence: 99%